2017
DOI: 10.1137/15m1050227
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Energy Scaling for Micropatterns in Transport Networks

Abstract: We consider two variational models for transport networks, an urban planning and a branched transport model, in which the degree of network complexity and ramification is governed by a small parameter ε > 0. Smaller ε leads to finer ramification patterns, and we analyse how optimal network patterns in a particular geometry behave as ε → 0 by proving an energy scaling law. This entails providing constructions of near-optimal networks as well as proving that no other construction can do better.The motivation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…To better understand the model behaviour, an energy scaling law for the network costs has been derived in [BW16b] (and will be reproved in this work, see Theorem 2.2.1) for the following simple problem geometry (Figure 1 left). In two-dimensional Euclidean space one considers as source and sink distribution the following measures concentrated on two lines, Figure 1: Left: Sketch of the considered setting, two measures µ 0 and µ 1 supported on lines at distance 1, as well as an exemplary transport network in between composed of elementary cells (dashed line).…”
Section: The Considered Settingmentioning
confidence: 99%
“…To better understand the model behaviour, an energy scaling law for the network costs has been derived in [BW16b] (and will be reproved in this work, see Theorem 2.2.1) for the following simple problem geometry (Figure 1 left). In two-dimensional Euclidean space one considers as source and sink distribution the following measures concentrated on two lines, Figure 1: Left: Sketch of the considered setting, two measures µ 0 and µ 1 supported on lines at distance 1, as well as an exemplary transport network in between composed of elementary cells (dashed line).…”
Section: The Considered Settingmentioning
confidence: 99%
“…Since x > 0, there is n ∈ N such that l x,n+1 < x ≤ l x,n . The assertion with d 1 := c 1 c 2 φ 1/3 follows from (73) using x ≤ l x,n = l x,n+1 /φ and recalling that r n ≤ 8 3 ηL y ≤ 3ηL y , and correspondingly L y − r n ≤ 8 3 ηL y . Now we turn to (10).…”
Section: Proofmentioning
confidence: 97%
“…These vectorial generalizations have confirmed that the Kohn-Müller scalar model indeed captures the correct scaling of the energy. A number of other problems have then been addressed with similar tools, including magnetization patterns in uniaxial ferromagnets [14,15,37], diblock copolymers [1,13], flux tubes in type-I superconductors [16,20,22,28], wrinkling in thin elastic films [4,6,7,34], dislocation microstructures [18,19], transport network structures [8,9], and compliance minimization [42].…”
Section: Introductionmentioning
confidence: 99%
“…Quite often, optimal solutions to problems involving a ramified transportation cost exhibit a fractal structure [2,3,4,12,15,16,17]. In the present note we analyze in more detail the optimization problem for tree branches proposed in [7], in the 2-dimensional case.…”
mentioning
confidence: 99%
“…In the formula (4), η(n) accounts for the intensity of light coming from the direction n. Remark 1. According to the above definition, the amount of sunlight S n (µ) captured by the measure µ only depends on its projection µ n on the subspace perpendicular to n. In particular, if a second measure µ is obtained from µ by shifting some of the mass in a direction parallel to n, then S n ( µ) = S n (µ).…”
mentioning
confidence: 99%